Seven more languages in seven weeks languages that are shaping the future - Tate, Bruce 1965-; Dees, Ian; Daoud, Frederic 1974-; Moffitt, Jack (Pragmatic Programmers, 2014)
Great programmers aren't born - they're made. The industry is moving from object-oriented languages to functional languages, and you need to commit to radical improvement. New programming languages arm you with the tools and idioms you need to refine your craft. While other language primers take you through basic installation and 'Hello, World, ' we aim higher. Each language in 'Seven More Languages in Seven Weeks' will take you on a step-by-step journey through the most important paradigms of our time. You'll learn seven exciting languages: Lua, Factor, Elixir, Elm, Julia, MiniKanren, and Idris.
"Version: P1.0 (November 2014).". - Place of publication from publisher's Web site. - Includes bibliographical references. - Print version record
Keywords: Programming languages (Electronic computers); COMPUTERS; Programming Languages; General